2005
DOI: 10.1086/428276
|View full text |Cite
|
Sign up to set email alerts
|

Color and Metallicity Distributions of M81 Globular Clusters

Abstract: ABSTRACT. In this paper we present catalogs of photometric and spectroscopic data for globular clusters (GCs) in M81. The catalogs include B-and V-band photometric and reddening data of 95 GCs, in addition to spectroscopic metallicities of 40 GCs. Using these data, we make some statistical correlations. The results show that the distributions of intrinsic B and V colors and metallicities are bimodal, with metallicity peaks at and Ϫ0.53, respectively, as has been demonstrated for our Milky Way and M31. The rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…It has an intermediate age and a metallicity [Z/H]= ‐ 0.8 ± 0.3, but the S/N in the spectrum is quite low and the errors of evolutionary parameters determination are large. KDG63‐3‐1168 appear to be younger and richer in metals compared to the many old clusters found in M81 (Georgiev, Tikhonov & Karachentsev 1991b; Georgiev et al 1991c; Schroder et al 2002; Chandar, Whitmore & Lee 2004; Ma et al 2005, 2006, 2007). Note that the mean metallicity of the GC is consistent with the mean metallicity of red giant stars in DDO71 ([Fe/H]=−1.17; Sharina et al 2008).…”
Section: Resultsmentioning
confidence: 89%
“…It has an intermediate age and a metallicity [Z/H]= ‐ 0.8 ± 0.3, but the S/N in the spectrum is quite low and the errors of evolutionary parameters determination are large. KDG63‐3‐1168 appear to be younger and richer in metals compared to the many old clusters found in M81 (Georgiev, Tikhonov & Karachentsev 1991b; Georgiev et al 1991c; Schroder et al 2002; Chandar, Whitmore & Lee 2004; Ma et al 2005, 2006, 2007). Note that the mean metallicity of the GC is consistent with the mean metallicity of red giant stars in DDO71 ([Fe/H]=−1.17; Sharina et al 2008).…”
Section: Resultsmentioning
confidence: 89%
“…Several tools are available to understand the chemical evolution of the M 81 disk: star clusters (Ma et al 2005;Nantais et al 2011), young supergiant stars (Davidge 2006), X-ray sources (Sell et al 2011), and color−magnitude diagrams fitting the HST-resolved stellar population (Kudritzki et al 2012). Nonetheless, emission-line targets such as HII regions and PNe have advantages over their stellar counterparts since PN and HII region spectra are analyzed in similar ways, making the comparison of the two sets of probes more direct than when comparing sources of different natures.…”
Section: Introductionmentioning
confidence: 99%
“…The bimodal test results in the two group: the metal-poor with a mean value of −1.47 and the metal-rich with a mean value of −0.62 (see also Barmby et al, 2000;Perrett et al, 2002;Fan et al, 2008). Ma et al (2005) presented a metallicity distribution of 94 M81 GCs being bimodal, with metallicity peaks at −1.45 and −0.53.…”
Section: Jun Mamentioning
confidence: 95%
“…Based on the estimated intrinsic colors, Chandar et al (2004) found that the M81 GC system has an extended metallicity distribution, which argues the presence of both metal-rich and metal-poor GCs. Ma et al (2005Ma et al ( , 2006Ma et al ( , 2007 presented detailed studies on M81 GCs based on the spectral and multicolor observations such as: the distributions of intrinsic B and V colors and metallicities of 95 GCs; the spectral energy distributions of 42 GCs in 13 intermediate-band filters from 4000 to 10,000 Å, using the CCD images of M81 observed as part of the Beijing-Arizona-Taiwan-Connecticut (BATC) multicolor survey of the sky; the spatial and metal abundance properties of 95 GCs. Nantais et al (2010b) presented a catalog of extended objects in and around M81 based on an HST ACS I-band mosaic, and found 233 good GC candidates.…”
Section: Jun Mamentioning
confidence: 99%
See 1 more Smart Citation